Complement Activation in the Disease Course of Coronavirus Disease 2019 and Its Effects on Clinical Outcomes - de Nooijer, Aline H (J Infect Dis, 2020)
BACKGROUND: Excessive activation of immune responses in coronavirus disease 2019 (COVID-19) is considered to be related to disease severity, complications, and mortality rate. The complement system is an important component of innate immunity and can stimulate inflammation, but its role in COVID-19 is unknown. METHODS: A prospective, longitudinal, single center study was performed in hospitalized patients with COVID-19. Plasma concentrations of complement factors C3a, C3c, and terminal complement complex (TCC) were assessed at baseline and during hospital admission. In parallel, routine laboratory and clinical parameters were collected from medical files and analyzed. RESULTS: Complement factors C3a, C3c, and TCC were significantly increased in plasma of patients with COVID-19 compared with healthy controls (P < .05). These complement factors were especially elevated in intensive care unit patients during the entire disease course (P < .005 for C3a and TCC). More intense complement activation was observed in patients who died and in those with thromboembolic events. CONCLUSIONS: Patients with COVID-19 demonstrate activation of the complement system, which is related to disease severity. This pathway may be involved in the dysregulated proinflammatory response associated with increased mortality rate and thromboembolic complications. Components of the complement system might have potential as prognostic markers for disease severity and as therapeutic targets in COVID-19.